COMPARATIVE ANALYSIS OF REAL TIME PCR AND ELISA FOR THE DETECTION OF PSEUDOMONAS AERUGINOSA IN NOT CHRONICALLY INFECTED CYSTIC FIBROSIS PATIENTS - MAHSHID KHODABAKHSHI; SELVAM ARJUNAN; KHALID IMRAN; RADHAKRISHNAN SENTHILKUMAR (International Journal of Pharma and Bio Sciences, 2014)
Detection of Pseudomonas aeruginosa using the serologic test have been found useful for differentiating colonization from infection, particularly in chronic disease. A quantitative polymerase chain reaction (qPCR) was compared with the Enzyme linked immunosorbent assay (ELISA) used routinely. The qPCR detected the targeted gene of P. aeruginosa outer membrane proteins, whereas the ELISA reacted with IgGs against soluble P. aeruginosa antigens. Among the 37 sera from the patients with not chronic lung disease studied, all those with ELISA reactivity were positive by qPCR. Thus, qPCR is more sensitive and specific than the ELISA, suggesting that the former technique may be useful for the early diagnosis of infection.